Quantitative evaluation of carbon nanomaterial releases during electric heating wire cutting and sawing machine cutting of expanded polystyrene-based composites using thermal carbon analysis. Issue 2 (1st February 2019) - Ogura, Isamu; Kotake, Mari; Ata, Seisuke
Abstract: Field measurements were conducted at a facility where expanded polystyrene-based carbon nanomaterial composites, namely, carbon nanotube and carbon black composites, were cut with an electric heating wire cutter or a circular sawing machine. The aerosol particles released during the cutting of the composites were measured using real-time aerosol monitoring, gravimetric analysis, thermal carbon analysis, and scanning electron microscopic observations. This study had two major goals: (1) to quantitatively evaluate the concentrations of airborne carbon nanomaterials during the cutting of their composites; (2) to evaluate the capability of thermal carbon analysis to quantify airborne carbon nanomaterials in the presence of expanded polystyrene-derived particles. The results of thermal carbon analysis showed that the concentrations of elemental carbon (an indicator of carbon nanomaterials) for all the respirable dust samples in both cutting processes were less than the limit of detection (∼2 µg/m 3 ), which is nearly equivalent to or lower than the occupational exposure limits for carbon nanotubes (1 to 50 µg/m 3 ). For total dust, which includes particles larger than respirable size, although the elemental carbon concentrations during heating wire cutting were low (<3 µg/m 3 ), those during sawing machine cutting were up to 58 µg/m 3 . In scanning electron microscopic observations, micron-sized particles composed of or including carbon nanotubes were detected only in aerosol particles collected during the sawing machine cutting. Therefore, heating wire cutting is considered preferable. This study demonstrated that thermal carbon analysis can quantify airborne carbon nanomaterials in the presence of expanded polystyrene-derived particles.